ANTI-CANCER EFFECT OF SOME PREPARED SULFATED OLIGOSACCHARIDES ON THREE DIFFERENT HUMAN CANCER CELL LINES - M. ALI, MAMDOUH; E. MAHMOUD, ABEER; H. ABDEL-HALIM, ABEER; A.FYIAD, AMAL (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Inhibitors of tumor angiogenesis and metastasis are rapdly emerging as important new drug candidates for cancer therapy. In our pursuit to develop new potential anticancer leads sulfated oligosaccharide we synthesized and characterized maltose SO4, raffinose SO4, stachyose SO4 and maltohexaose SO4. Cytotoxic evaluations of these compounds over a panel of three human cancer cell lines including liver cancer HepG2; breast cancer MCF-7 and lung cancer A549 were carried out with investigation the ability of these compounds in inhibiting tumor growth, metastasis, and angiogenesis. The sulfated compounds exploited potent to moderate growth inhibitory activity in the three cell lines, in particular maltohexaose SO4 exhibited superior potency to doxorubicin (IC50 = 4.20, 4.70 and 6.80 Âµg/ml, respectively in HepG2, MCF-7 and A549 against 4.50, 4.80 and 7.00 for doxorubicin respectively). On the other hand, the unsulfated oligosaccharides have no cytotoxicity activity. The anticancer activity of these compounds was accompanied by over production of free radicals allowed tumor cells death as monotoring by significantly increased in the activity of superoxide dismutase (SOD) and the levels of hydrogen peroxide (H2O2), and nitric oxide (NO), while the activities of catalase (CAT), glutathione peroxidase (GSH-Px) and the level of reduced glutathione (GSH) were significantly lowered with decline the total protein, DNA and RNA content. Furthermore, the prepeared compounds resulted in reduction in the activity of tyrosine kinase (TRK) and cytochrome P450 2E1 (CYP 2E1) which implicated in the development of cancers. Also, the compounds decreasing the level of vascular endothelial growth factor (VEGF) as a marker of angiogenesis and inhibition in a metastatic as measured by reduction in the activity of heparanase and elastase enzymes. In conclusion, the results suggested that the synthesized compounds can be used as good candidate for novel therapeutic strategies for cancer especially maltohexaose SO4 which possessed significant anticancer activity through regulation angiogenesis and metastasis of cancer. Â Key Words: Sulfated oligosaccharide â€“ anticancer â€“ angiogenesis - metastasis -antioxidantsÂ Â Â Â Â Â Â Â